Mechanism of Transcranial Magnetic Stimulation in the Treatment of Neuropathic Pain - SUN Yu-jia; ZHANG Jun-feng; YAN Long; FAN Shi-yu; QIAN Yu-lin; CONG Shan; YU Tao (康复学报)
Neuropathic pain （NP） is a persistent and refractory chronic pain condition resulting from damage or disease within the somatosensory nervous system. Its complex pathophysiology，coupled with low clinical remission rates，significantly impairs the physical and mental well-being of affected individuals. Transcranial magnetic stimulation （TMS），a well-established non-invasive neuromodulation technique，generates brief magnetic pulses that penetrate the skull，inducing changes in cortical neuron potentials. This can influence both the function and structure of the nervous system，providing relief from NP symptoms and improving associated mood disorders. However，the neurobiological mechanisms underlying TMS-induced analgesia have not yet been fully elucidated，and there is no consensus on these mechanisms. This review aims to synthesize current understanding of the neurobiological mechanisms by which TMS alleviates NP，based on its operational principles. The mechanisms discussed include modulation of synaptic plasticity，functional reorganization of neural networks （inducing cortico-cortical functional connectivity and subcortical functional connectivity），adjustment of afferent nerve fiber sensitivity，alteration of neurotransmitter levels，and effects on neuroimmune interactions. These mechanisms collectively provide a foundation for the application of TMS in the treatment of NP. Despite the promising findings，several limitations persist in the current body of research. Studies on synaptic plasticity are not sufficiently detailed，and investigations into afferent nerve fiber sensitivity require further refinement. Additionally，the exploration of neuroimmune responses remains limited. Future research should address these gaps through multicenter，large-scale studies，employing advanced technologies such as electroencephalography （EEG） to better understand the intrinsic mechanisms by which TMS modulates neural networks. Furthermore，the application of paired-pulse TMS in clinical studies related to NP should be promoted，thereby providing more robust evidence-based support for the use of TMS in the treatment of neuropathic pain.